A Comparative Study on the Structure-Performance Relationships of Chemically and Electrochemically Coagulated Al(OH)3 Flocs - Can, Orhan Taner; Bayramoglu, Mahmut (Amer Chemical Soc, 2014)
In this paper, various physical and chemical characteristics of electro-coagulated (ECC) and chemical-coagulated (CC) aluminum hydroxide flocs were explored comparatively in the context of their impacts on the pollutant removal performance of the processes. First, the sedimentation rate, floc size and zeta potential of the flocs at different pH values were measured in solution. Furthermore, flocs dried at 105 degrees C were characterized by various techniques such as TGA,FT-IR, SEM, XRD, BET and XPS as well as by chemical analysis. It was found that ECC flocs were bigger in size, faster in sedimentation and better pressed, while they had higher BET area, less water and higher isoelectric pH than CC flocs. Furthermore, pollutant removal tests using various chemicals such as benzoquinone, hydroquinone and a reactive dye showed that ECC flocs outperformed CC flocs, due to superior physical-chemical characteristics.
Keywords: Textile Waste-Water; Aqueous-Solutions; Dye Solutions; Zero Point; Basic Dye; Electrocoagulation; Removal; Aluminum; Decolorization; Wastewaters